Chemical Characteristics of Gluten-Free Noodle Made from Mocaf and Porang Flour - Rosa Andiani; Dedin Finatsiyatull Rosida; Muhammad Alfid Kurnianto (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
The development of gluten-free noodles has become an option for those with gluten intolerance or aiming to reduce their gluten intake. Mocaf (Modified Cassava Flour), rich in starch and porang flour with glucomannan content, can be used as the base ingredient for making gluten-free noodles. This research aims to determine the optimal proportions of gluten-free noodles based on mocaf and porang flour. This research used a completely randomized design (CRD) with 1 factor, namely the proportion of mocaf flour and porang flour in 3 levels (60:40, 50:50, and 40:60). Observation data were analyzed using analysis of variance (ANOVA) and Tukey's further test at the 5% level. The results showed that the lowest water content of the noodles was found in treatment 60: 40 mocaf and porang flour, with a moisture content of 7.52%. The highest starch content was found in the treatment of 60:40 mocaf and porang flour, with a starch content of 44.04%. The highest crude fibre content was found in the 40:60 mocaf and porang flour treatment, with 6.52% crude fibre content.